2009
DOI: 10.1002/prop.200900048
|View full text |Cite
|
Sign up to set email alerts
|

Duality between Wilson loops and gluon amplitudes

Abstract: An intriguing new duality between planar MHV gluon amplitudes and light-like Wilson loops in N = 4 super Yang-Mills is investigated. We extend previous checks of the duality by performing a two-loop calculation of the rectangular and pentagonal Wilson loop. Furthermore, we derive an all-order broken conformal Ward identity for the Wilson loops and analyse its consequences. Starting from six points, the Ward identity allows for an arbitrary function of conformal invariants to appear in the expression for the Wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 233 publications
(741 reference statements)
0
28
0
Order By: Relevance
“…It will be interesting to study the application of the ideas of on-shell recursion at loop level to maximally supersymmetric Yang-Mills theory in four dimensions as it opens a window to prove conjectured properties of the integrals and integrands such as dual conformal invariance and its one-loop breaking (see [49] and references therein and thereto).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to study the application of the ideas of on-shell recursion at loop level to maximally supersymmetric Yang-Mills theory in four dimensions as it opens a window to prove conjectured properties of the integrals and integrands such as dual conformal invariance and its one-loop breaking (see [49] and references therein and thereto).…”
Section: Discussionmentioning
confidence: 99%
“…for the hexagonal light-like Wilson loop, which is dual to the six-gluon MHV amplitude [8,9] (for reviews see [26,27] and references therein, and [28,29] for recent developments). In [30], a remarkably simple form of the six-point remainder function [8,9] was given, based on previous work [31].…”
Section: Jhep04(2011)083mentioning
confidence: 99%
“…In N " 4 supersymmetric Yang-Mills theory, the connection between scattering amplitudes and Wilson loops goes even further, cf. the reviews [59,60] for a more detailed discussion of the ideas sketched below. The first signs of the conjectured duality were observed by Alday and Maldacena [61], who found that maximally helicity violating (MHV) gluon scattering amplitudes at strong coupling are described by the area of certain minimal surfaces and hence identical to the Maldacena-Wilson loop over the respective boundary contour.…”
Section: Duality To Scattering Amplitudesmentioning
confidence: 99%